EFEK KONSENTRASI DAN WAKTU APLIKASI PUPUK ORGANIK CAIR KULIT PISANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUMIS KUCING (Orthosiphon aristatus) - Detri Saputra; Entang Inoriah Sukarjo; Masdar Masdar (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[EFFECT OF CONCENTRATION AND APPLICATION TIME OF ORGANIC FERTILIZER LIQUID BANANA PEELS ON GROWTH AND YIELD OF JAVA TEA (Orthosiphon aristatus)]. Java tea are medicinal plants that have many health benefits but java tea production is very low. Efforts are made to increase the growth and yield of java tea, namely the use of liquid organic fertilizer (LOF) banana peels. This study aims to obtain concentration, application time of LOF banana peels, and interactions between the two that produce high growth and yield of java tea. The study was conducted from November 2018 to February 2019 in the city of Bengkulu. The experiments were arranged based on a completely randomized design factorial pattern. The first factor is the LOF concentration of banana peels 25 mL/L, 50 mL/L, 75 mL/L, and 100 mL/L. The second factor is the time of LOF application which consists of 1 week application, 2 weeks application, and 3 weeks application. The results showed that independently giving concentration and application time and interaction did not significantly influence the variable thickness of leaves, total leaf area, shoot length, number of leaves, fresh plant weight, root length, and dry plant weight.